(untitled) (Advances in Civil and Architectural Engineering, 2023)
Owing to its high energy dissipation characteristics, the passive damper is an effective means of mitigating natural hazards for structures. In this study, a novel magnetic pole repulsive damper (MPRD), designed for reducing structural responses during natural hazards such as earthquakes, was developed and its performance was validated. The MPRD is an effective solution for seismic protection that works on the principle of magnetic repulsion and has a higher energy dissipation capacity than conventional dampers. The MPRD was fabricated using mild steel, neodymium magnets, and a set of helical springs. Two scaled reinforced concrete frames were tested using a 50 kN loading actuator. One frame was equipped with the MPRD, while the other served as a conventional frame for comparison. The frame with the MPRD showed reduced displacements. Compared with the conventional frame, that with the MPRD exhibited an increase in load of 40 % and an increase in energy dissipation of 6,44 %. Further, an increase in lateral stiffness, a 19,23 % increase in stiffness degradation, and changes in crack patterns were observed in the frame with MPRD compared to the conventional frame. The study’s success in validating the MPRD performance in reducing structural responses in moderate to high seismicity regions makes it a promising solution for building seismic protection.